Determinants of public trust in complementary and alternative medicine - Groenewegen Peter P; van der Schee Evelien (BMC, 2010)
Abstract Background In the Netherlands, public trust in conventional medicine is relatively high. There is reason to believe that public trust in complementary and alternative medicine (CAM) is rated lower. The aim of this study is to gain insight into public trust in CAM and the determinants that lie at the root of it. We hypothesized that public trust in CAM is related to (perceived) institutional guarantees, media information on CAM, information from people's social network, personal experiences, the role of general practitioners (GPs) and trust in conventional medicine. Methods A postal questionnaire on public trust in CAM was mailed to 1358 members of the Health Care Consumer Panel. 65% of the questionnaires were returned. Data were analysed using frequencies, ANOVA, post hoc testing and linear regression analyses. Results In the total sample, the level of public trust in CAM was a 5.05 on average on a scale of 1-10. 40.7% was CAM user (current or past) and displayed significantly higher levels of trust toward CAM than CAM non users. In the total sample, public trust in CAM was related to institutional guarantees, negative media information, positive and negative information reported by their social network and people's personal experiences with CAM. For non users, trust is mostly associated with institutional guarantees. For users, personal experiences are most important. For both users and non users, trust levels in CAM are affected by negative media information. Public trust in CAM is for CAM users related to positive information and for non users to negative information from their network. Conclusions In the Netherlands, CAM is trusted less than conventional medicine. The hypotheses on institutional guarantees, media information, information from the network and people's personal experiences are confirmed by our study for the total sample, CAM non users and users. The other hypotheses are rejected.